Subjectivity and Sexual Difference: Analyzes of Phallogocentrism in Psychoanalysis and Poststructuralist Feminism - Christofoletti da Silva Gabriel, Laura; de Souza, Mériti; Angeli, Gustavo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2022)
Reading about the sexual difference occupies a central place in theories about the subjective constitution and phallogocentrism construction. The article problematizes the reading of sexual differences. It questions the phallogocentric assumption regarding the elaboration of subjectivity, binarism, and hierarchy that anchors the male and female pair. It was possible to perform the qualitative-theoretical research by selecting works of authors referenced in psychoanalysis to analyze the relationship between sexual difference and the subject. Also, it was possible to select works by contemporary authors regarding contemporary psychoanalysis and poststructuralist feminist studies by considering their phallogocentrism criticisms.It is possible to conclude by the need to question the separation between nature and culture, body and symbolic, sex and genderto critically base the reading and work on sexual difference.